Robot Pengukur Arah Kiblat Berbasis Offline Untuk Penyandang Tuna Netra - Ikhsan Mahaendra; Ahmad Adib Rofiuddin (Jurnal Alwatzikhoebillah : Kajian Islam, Pendidikan, Ekonomi, Humaniora, 2024)
The Qibla is fundamental in matters of Muslim worship so it needs to be given more attention. This research is intended to design a Qibla robot to determine the Qibla direction for blind people. This research uses research and development research methods, namely, by designing an offline-based robotic Qibla direction measuring device for the blind. This research produced findings in the form of a Qibla measuring tool called "Kibla Robot". The disadvantage of this Qibla Robot is that, firstly, it cannot be used in sloping, uneven or wavy places. Second, it cannot be used in rooms where there are too many magnetic fields, and third, the battery power runs out quickly, affecting the working function of the tool, fourth, when the latitude and longitude of the location are different, it must be reprogrammed. The first advantage of this Qibla Robot is its ergonomic shape. Second, he helps blind people determine the direction of the Qibla. Third, it can be used in areas with minimal internet signal, fourth it can be used indoors and outdoors. The level of accuracy of measurements on the Qibla Robot compared with the Theodolite is that there is no difference, and calculations in retrieving Solar Azimuth data from manual calculations and the Stellarium Application have a difference of 0 o 35' 36.09". A difference of less than one degree indicates that this tool is accurate.